Data from: No evidence for sibling or parent-offspring coadaptation in a wild population of blue tits, despite high power. - Thomson, Caroline; Hadfield, Jarrod D.; Thomson, Caroline E. (Dryad, 2018)
Parent and offspring behaviours are expected to act as both the agents and
targets of selection. This may generate parent-offspring coadaptation in
which parent and offspring behaviours become genetically correlated in a
way that increases inclusive fitness. Cross-fostering has been used to
study parent-offspring coadaptation, with the prediction that offspring
raised by non-relatives, or parents raising non-relatives, should suffer
fitness costs. Using long-term data from more than 400 partially crossed
broods of blue tits (Cyanistes caeruleus) we show there is no difference
in mass or survival between crossed and non-crossed chicks. However,
previous studies for which the evidence for parent-offspring coadaptation
is strongest compare chicks from fully crossed broods with those from
non-crossed broods. When parent-offspring coadaptation acts at the level
of the brood then partial cross-fostering experiments are not expected to
show evidence of coadaptation. To test this, we performed an additional
cross-fostering experiment (163 broods) in which clutches were either
fully crossed, non-crossed, or partiallycrossed. In agreement with the
long-term data, there was no evidence for parent-offspring coadaptationon
offspring fitness depsite high power. In addition there was no evidence of
effects on parental fitness, nor evidnce of sibling coadaptation, although
the power of these tests was more modest.
Chick dataChick data (both weights and survival).chicks.RDataAdult
dataAdult data (both fecundity and survival).adults.RDataPedigree
dataPedigree dataped.RDataR codeAnalysis scriptsDryadRcode.R
Keywords: parent-offspring coadaptation; blue tit; cross-fostering; maternal effects; Cyanistes caeruleus; Cyanistes caeruleus; sibling competition; parental effects